2021
DOI: 10.1093/rheumatology/keab401
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of gastrointestinal manifestations in a large Spanish cohort of patients with systemic lupus erythematosus: what do we know?

Abstract: Objective SLE can affect any part of the gastrointestinal (GI) tract. GI symptoms are reported to occur in >50% of SLE patients. To describe the GI manifestations of SLE in the RELESSER (Registry of SLE Patients of the Spanish Society of Rheumatology) cohort and to determine whether these are associated with a more severe disease, damage accrual and a worse prognosis. Methods We conducted a nationwide, retrospective, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Regarding GI manifestations associated with SLE and damage accrual, a recent Spanish retrospective cohort study of 3658 SLE patients found that 3.7% developed GI damage. 15 This low prevalence is consistent with the findings of previous cohort studies. 16 , 17 Furthermore, they observed that GI damage is associated with poorer prognosis and clinical involvement of other target organs in SLE, such as vasculitis, renal disease, and serositis.…”
Section: Introductionsupporting
confidence: 92%
“…Regarding GI manifestations associated with SLE and damage accrual, a recent Spanish retrospective cohort study of 3658 SLE patients found that 3.7% developed GI damage. 15 This low prevalence is consistent with the findings of previous cohort studies. 16 , 17 Furthermore, they observed that GI damage is associated with poorer prognosis and clinical involvement of other target organs in SLE, such as vasculitis, renal disease, and serositis.…”
Section: Introductionsupporting
confidence: 92%
“…The gastrointestinal symptoms were reported to occur in >50% of SLE patients, and lupus enteritis was possibly identified as an initial manifestation in SLE ( 37 , 38 ). The histological examination showed that both probiotics restored the colonic histomorphology to a certain extent ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…94 Meta-regression analyses of the association between CD prevalence in patients with SLE and publication year (p=0.58), study population size (p=0.26), prevalence of CD in the general population (p=0.78), proportion of females (p=0.66) and quality assessment score (p=0. 84) showed no significant associations (online supplemental figure S4A-E). We found no significant publication bias in the funnel plot (figure 2) and Egger's test (p=0.25).…”
Section: Prevalence Of CD In Slementioning
confidence: 95%